2019
DOI: 10.1111/aas.13509
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of bradycardia in pediatric patients undergoing intranasal dexmedetomidine sedation

Abstract: Background: Dexmedetomidine is widely used for non-invasive pediatric procedural sedation. However, the hemodynamic effects of intravenous dexmedetomidine are a concern. There has been a growing interest in the application of intranasal dexmedetomidine as a sedative in children. Objective: To investigate the incidence of bradycardia in children undergoing intranasal dexmedetomidine sedation and to identify the associated risk factors. Methods: Data pertaining to pediatric patients who underwent intranasal dexm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 26 publications
3
22
1
Order By: Relevance
“…The uctuations in the HR, SBP, and DBP values in the patients of the nasal drops group were not observed to exceed 15% of the baseline value at any point in time, which was identical to the ndings of the study by Yao et al Another study showed that the HR and SBP uctuations with dexmedetomidine 2 µg / kg nasal use were within 17.5% and 16.1% [8]. Based on the outcomes of the study by Lei et al, bradycardia and blood pressure values of all the children in the 9986 cases with dexmedetomidine sedation were within the normal range [17], demonstrating that the effect of dexmedetomidine nasal use on the hemodynamics was insigni cant. Compared with the baseline value, the HRs in the intravenous group patients decreased most signi cantly at 1 min to 26.52% (79.3 ± 14.08 vs. 107.92 ± 14.91; p < 0.05), and rose to 12.11% (94.85 ± 8.83 vs.) at 5 min, which is similar to the outcomes of the study by Jooste [18].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The uctuations in the HR, SBP, and DBP values in the patients of the nasal drops group were not observed to exceed 15% of the baseline value at any point in time, which was identical to the ndings of the study by Yao et al Another study showed that the HR and SBP uctuations with dexmedetomidine 2 µg / kg nasal use were within 17.5% and 16.1% [8]. Based on the outcomes of the study by Lei et al, bradycardia and blood pressure values of all the children in the 9986 cases with dexmedetomidine sedation were within the normal range [17], demonstrating that the effect of dexmedetomidine nasal use on the hemodynamics was insigni cant. Compared with the baseline value, the HRs in the intravenous group patients decreased most signi cantly at 1 min to 26.52% (79.3 ± 14.08 vs. 107.92 ± 14.91; p < 0.05), and rose to 12.11% (94.85 ± 8.83 vs.) at 5 min, which is similar to the outcomes of the study by Jooste [18].…”
Section: Discussionsupporting
confidence: 84%
“…In the ward, the EA incidences in the nasal, intravenous injection, and control groups were 20.00%, 17.50%, and 70.00%, respectively. Statistical differences between the nasal drop and control groups (p < 0.05, OR = 0.107, 95% CI [0.038-0.300]), and intravenous injection, and control groups (p < 0.05, OR = 0.091, 95% CI [0.032-0.262]) were recorded.…”
Section: Resultsmentioning
confidence: 97%
“…Sedation failure with supplemental dose was defined as follows: ① After supplemental dosing with chloral hydrate, the patients could not achieve satisfactory depth of sedation within 30 min;② Failure to complete the diagnostic procedure even after achievement of the anticipated depth of sedation [5]; ③ The occurrence of severe adverse events which prevents the diagnostic procedures continuing; ④ The need of other medications in addition to chloral hydrate.…”
Section: Definitionsmentioning
confidence: 99%
“…Midazolam, chloral hydrate, and dexmedetomidine that can be administrated orally or transmucosally are considered as the best choices. However, sedative-hypnotics, such as midazolam, chloral hydrate, dexmedetomidine, have a certain failure rate about 1% [3], 3.4% [4], 5.7% [5], respectively. Failure of sedation may lead to cost and time detriment, as well as dissatisfaction from guardians.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation